Estudio comparativo entre agentes blanqueadores caseros naturales y agentes blanqueadores aplicados en el consultorio dental, para determinar su efectividad. Periodo marzo-julio 2016. - Juárez Macas, Karla Lorena (2016)
This research was aimed to establish the efficacy of homemade dental whiteners or clinical dental whiteners throughout its application. This research is an experimental medicine-epidemiological study applied to 30 patients divided into two groups, one group comprised 15 patients were administered the tooth whitening dental use and also the other group comprised 15 patients were administered the natural home whitening. The information was gathered in before elaborated cards of observation and one took photography’s of before and after the treatment. The changes were identified in both groups of study, were achieved dental whitening by both types of whitening. The most effective was the clinical dental whitening with an 86,67%, while the natural whitening effectiveness had a half a 80.00%. Furthermore whitening dental use when applied caused mild dentine sensitivity for a short time; however natural products did not cause any adverse reaction, because they are less abrasive than dental use. Concluding that dental whitening is most effective; it is more abrasive than naturally whitening bleach, and can be used for the removal of extrinsic stains. Key words: dental whitening, homemade dental whiteners, clinical whiteners.